Analisis Yuridis Putusan Mahkamah Konstitusi No. 80/PUU-XIV/2016 tentang Kewarganegaraan - Anisah Magfiroh; Inayatul Anisah (Rechtenstudent, 2023)
In 2016, there was a case regarding the questioning or loss of the citizenship status of a child, which resulted from mixed marriages between Indonesian citizens and foreign nationals (France). A person's citizenship status is very important, because there is legal protection by the state for its citizens both inside and outside the country. The research method of Library Research and the type of research is normative law to arrive at a conclusion and seek information about the basis or legal basis that emphasizes analysis related to the object of study studied by examining Constitutional Court Decisions and journals related to citizenship status. The results of this study include: 1) The issuance of the Constitutional Court Decision Number 80/PUU-XIV/2016 concerning Citizenship was caused by the loss of the constitutional rights of a child from mixed marriages because of the phrase in article 41 of Law Number 12 of 2006 which requires register with the minister 4 years after the law was promulgated, even though it is already known that in article 6 it has also been stated regarding the right to choose citizenship after the age of 18, but it needs to be outlined what the meaning of article 6 only applies if article 41 is done first for children born before 2006. 2) Implications of the Constitutional Court Decision Number 80/PUU-XIV/2016 against mixed marriages in Indonesia eliminates discrimination against women by providing legal protection and clarity for children of mixed marriages.